Konsep Pendidikan Profetik Dalam Membentuk Karakter - Wahyu Ningsih; Aang Setiawan; Dita Adellia Nabilla Siva (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The prophet is a human of noble character and ideal physically and psychologicall, who has the capability to communicate effectively with God and the angels and becomes the reference for man based on the holy book revealed to him. With his potentials, the prophet is capable of passing the vissionary teachings to build the community so that the members can be more holistically prosperous. With his four main characters, i.e., truthful, trustworthy, informative, and intelligent, the prophet becomes the figure who always follows the guidance of conscience and truth, maintains professionalism and commitment, masters the communication skills, and is simultaneously capable of solving problems. These are the prophetic values which are expected to inspire the character education developed. Prophetic education will operationally be internalized in the education elements such as goals, learners,educators, curriculum, media,, and evaluation, all of which contain the main prophetic aspects. Character education in this prophetic perspective is a new alternative that is worth considering.